Perubahan Unsur Hara Makro (C-Organik N, P, K, DAN C/N) Tanah Salin Entisols Sidondo Akibat Pemberian Kompos Dan Sulfur Serta Pengaruhnya Terhadap Pertumbuhan Tanaman Jagung (Zea mays L.) - Amar Bhakti; Muhammad Basir Cyio; Saiful Darman (Universitas Tadulako, 2019)
This study aims to determine the effect and interaction of composting and sulfur to changes in the macro nutrients in the soil saline Entisols Sidondo also to know the growth of maize ( Zea mays L ) in saline soil conditions by granting the application of compost and sulfur. The research was conducted from January to March 2016 , samples were collected from the ground in the village Sidondo, District Dolo, Biromaru Sigi regency, Central Sulawesi Province. Implementation of the experiment was conducted at the Experimental Farm, located in the Village Mamboro Western District of North Palu Palu City and analysis of soil and plant tissue analysis conducted at the Laboratory of Nature and Natural Resources and Environment, Faculty of Agriculture, University Tadulako, Palu. This research is compiled in a Complete Randoised Design (CRD) with 8 treatments and 3 replications. The treatments used are: Po= 0 ton ha-1, P1= compost 20 tons ha-1, P2= compost 40 tons ha-1, P3= compost 60 tons ha-1, So= 0 kg S ha-1, S1= Sulfur 200 kg S ha-1, S2= Sulfur 300 kg S ha-1, S3= Sulfur 400 kg S ha-1. Research shows the interaction between compost and sulfur real impact on the C-organic, nitrogen (N), phosphorus (P), and potassium (K). While the C / N no interaction Treatment dosage of 60 tons ha-1, compost gives the highest yield on the uptake and concentration of N and P in plant tissues of maize while giving high sulfur results in a dose of 300 kg S ha-1.